Vilifying the pedophiles and perverts: a nationwide test of the community attitudes toward sex offenders (catso) scale - Klein, Jennifer L. (Criminology, criminal justice, law & society, 2015)
Sex offenders are often reviled and have difficulties reentering society post-incarceration—due in part to the negativity directed toward them by community members. This study uses the Community Member Attitudes toward Sex Offenders (CATSO) Scale (Church et al., 2008) to test perceptions of a national sample of participants regarding sex offenders, their crimes, and the official responses to their abuses. Using legal and stereotypical knowledge as the main variables predicting the elements of the CATSO Scale, the results suggest an inverse relationship between the level of accurate knowledge and negative attitudes toward sex offenders. Parental status and race also play key roles in predicting the elements of the CATSO scale. Additional research findings, policy implications, and limitations will be discussed.